Penerapan Sosıal Medıa Management Kassımura - Muhammad Ardiansyah; Fedric Tan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Kassimura is a business engaged in the furniture sector which has been running for 12 years. The obstacle faced by Kassimura while carrying out his business activities is the sale promotion which is carried out using Facebook ads which include Instagram, Facebook is not effective because it makes advertisements that are not true. The methodology applied in this research is a qualitative descriptive analytical method which aims to solve practical problems in the modern world. Results of the study in form of the design and advertisement through facebook ads. The implementation of the research gave many positive impacts where the owner of the Kassimura company felt that sales had increased more than before because of the good and correct way of advertising accompanied by an attractive design